Impairments of auditory-verbal short-term memory: Do selective deficits of the input phonological buffer exist?. (March 2019) - Shallice, Tim; Papagno, Costanza
Abstract: The existence of the functional syndrome of auditory-verbal short-term storage impairment was used as strong supporting evidence for the presence of a phonological buffer in the first version of the Baddeley–Hitch working memory model. In later versions the syndrome corresponded to the selective impairment of the phonological input buffer. The present paper considers whether the correspondence between the functional syndrome, represented by 20 published cases, and a Baddeley–Hitch model component is still of value to memory theory. The following potential problems for the theoretical utility of the correspondence are considered: 1. The apparent rarity of examples of the syndrome: are they outliers? 2. Is short-term memory not merely the activation of long-term memory traces? 3. Could the syndrome be due to failed interaction between perceptual and motor speech processing? 4. Do some aspects of the syndrome not fit the Baddeley–Hitch model predictions? 5. Has the Baddeley–Hitch model not been replaced by more powerful connectionist models? 6. Could the syndrome arise from weakened speech perception processes? It is argued that there are difficulties for each of these possibilities. It is held that the correspondence retains its value.